Analysis of Biomass Briquette Mixed Bagasse and Sugarcane Peel on the Performance of Forced Top-Lit Updraft Gasifier Stove - Hardiatama, Intan; Enruico, Aron; Hermawan, Yuni; Trifiananto, Muhammad; Syuhri, Skriptyan N. H. (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
The population growth in Indonesia from 270 million in 2020 to 279 million in 2024 has increased LPG consumption, potentially leading to future fuel shortages. The top-lit updraft (TLUD) gasifier stove using renewable biomass materials, offers a sustainable alternative. Biomass such as bagasse and sugarcane peel can be optimized into charcoal briquettes with high calorific value and low emissions. The calorific value of briquettes can be further enhanced by blending other high–calorific biomass materials. This experimental research focuses on testing the calorific value of raw bagasse and sugarcane peel before carbonization, as well as briquette mixtures (70:30, 50:50, 30:70) using a bomb calorimeter. The fuel briquettes are tested by operating the TLUD gasifier stove, measuring performance in terms of water boiling time (WBT) and flame characteristics. Results show that the 30:70 bagasse-to-sugarcane peel composition has the highest calorific value (6,242.292 cal/gram), followed by the 70:30 composition (6,094.753 cal/gram) and the 50:50 composition (5,657.935 cal/gram). The 30:70 ratio also achieved the longest flame duration (119 minutes 32 seconds), the highest combustion chamber temperature (570.2°C), and the greatest flame height (11.468 cm). The TLUD stove demonstrated an efficiency of 56.41%, with a char weight of 61 grams and a water temperature increase from 28.4°C to 90.4°C in 10 minutes 45 seconds. These briquettes met the SNI 01-6235-2000 standard, which requires a minimum calorific value of 5000 cal/g.